Biocompatible and resorbable composite material and method for obtaining same - Patents.com
By dissolving the polymer in the solvent and removing the solvent with anti-solvent, the thermal oxidation problem of polymer caused by high temperature treatment in the prior art is solved, and higher mechanical properties and absorption time are achieved, and the stability of the composite material is improved.
Patent Information
- Application Number
- JP2024547788
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-25
- Filing Date
- 2023-02-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-02-16
AI Technical Summary
Prior Art When making glass fiber reinforced polymer composites, it is necessary to heat the glass fiber to high temperatures to melt the polymer, resulting in thermal oxidation damage to the polymer, reducing its mechanical properties and in vivo absorption time.
By dissolving the polymer in a solvent, applying the solution on glass fibers, and removing the solvent with an anti-solvent, forming a solid composite material, thereby avoiding high temperature treatment.
This method reduces thermal oxidation damage of polymers, improves the mechanical properties and in vivo absorption time of composite materials, while allowing for better fiber distribution and low-level residual monomers, enhancing the stability of the material.
Smart Images

Figure 2025507554000001 
Figure 2025507554000002 
Figure 2025507554000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for obtaining a solid polymer composite comprising a plurality of biocompatible and resorbable glass fibers embedded in a biocompatible and resorbable matrix polymer. The present invention further relates to a glass fiber reinforced polymer composite obtained by said method, and to a medical device comprising said composite. [Background technology]
[0002] The field of medical devices, such as implants, is a very dynamic and rapidly growing field. It is expected that the field will continue to grow as the average human age continues to increase. As a result, there is a great drive to improve the properties of medical implants and to improve the methods of manufacturing medical implants.
[0003] Many kinds of materials, such as metal alloys, ceramics, and polymers, are known to be used to manufacture medical implants. Metal alloys are the traditional choice for manufacturing orthopedic implants, such as pins, screws, and plates, because they are highly suitable for withstanding external loads due to their high strength. However, metal alloys are typically harder (i.e., they have a higher modulus of elasticity) than the bones to which they are connected. As a result, stress-shielding reduces bone density at the repair site. Also, metal alloys are typically not degraded in the body. Therefore, to avoid and lack of bone resorption, metal alloys generally need to be removed after bone healing, which requires reoperation.
[0004] New materials have been developed that better match the mechanical properties of bone and can be absorbed by the body over time. These materials minimize stress shielding issues and eliminate the need for revision surgery.
[0005] EP 2 243 500 describes a method for producing an implantable composite material comprising a polymer matrix and glass fibres. Here, the glass fibres are produced separately and then cut to lengths of 10 mm before being mixed with the matrix polymer in an extruder. Alternatively, the fibres are produced separately and mixed with the molten polymer in a cross-head die. In either case, the matrix polymer must be in a molten state in order to be processed in an extruder, i.e. the matrix material must be a thermoplastic which requires a relatively low viscosity using high processing temperatures. Thus, the process of EP 2 243 500 is limited by the requirement that the matrix polymer be a thermoplastic polymer. In addition, the heat required to achieve the necessary low viscosity of the thermoplastic polymer can cause thermo-oxidative damage. As a result, the matrix polymer suffers from polymer degradation and associated molecular weight loss, which reduces mechanical performance and shortens in vivo absorption times. Summary of the Invention [Problem to be solved by the invention]
[0006] Therefore, there is a need for better methods of producing polymer-based composite materials that allow for better control over the composition and performance of the composite final product. [Means for solving the problem]
[0007] The above-mentioned problems are solved by using the method of the present invention, which is a method for obtaining a solid polymer composite comprising a plurality of biocompatible and resorbable glass fibers embedded in a biocompatible and resorbable matrix polymer, comprising the steps of: a) providing a plurality of biocompatible and resorbable glass fibers that are compatible with the matrix polymer; b) providing a mixture comprising the matrix polymer in a solvent; c) applying the mixture onto the plurality of glass fibers; and d) removing the solvent from the mixture using an anti-solvent to obtain the solid composite material. The process includes the steps of:
[0008] As can be seen, the above method eliminates the need for heat-driven, melt-processing and for using an extruder to feed the polymer melt to the melt pultrusion die. Thus, the matrix polymer does not need to be heated to high temperatures, thereby significantly reducing the risk of polymer degradation. Instead, the matrix polymer solution can be applied at a relatively low and manageable temperature, such as room or ambient temperature, at which polymer decomposition does not begin. In addition, if desired, the glass fibers can be oriented and spread out, and a manageable mixture comprising matrix polymer and solvent can be applied. If desired, multiple mixtures can be applied, resulting in thicker layers of matrix polymer.
[0009] It is possible to use the method according to the invention with discontinuous (e.g. chopped) fibres. Additionally and / or alternatively, the method may also be used with longer (e.g. continuous or woven or knitted) fibres, which may be beneficial as it allows for better tailoring of the properties of the glass reinforced polymer composite (GRP) material and therefore does not require breaking the glass fibres in such shorter fibres.
[0010] The present invention further relates to a polymer composite material comprising a plurality of biocompatible and resorbable glass fibers in a biocompatible and resorbable polymer matrix, the composite having a matrix polymer monomer content of less than 2% by weight, more preferably less than 1% by weight, and even more preferably less than 0.5% by weight relative to the matrix polymer. A composite with a low monomer content is beneficial, since a high monomer content is an indication of undesirable degradation of the matrix polymer, which may result in an uncontrolled loss of mechanical strength of products, such as medical implants, made from the polymer composite material. The composite can be obtained or be obtained by the method of the present invention.
[0011] The composites of the invention are particularly useful in medical devices, such as medical implants, including orthopedic implants and scaffoldings. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention relates to a method for obtaining a solid polymer composite material comprising a plurality of biocompatible and resorbable glass fibers embedded in a biocompatible and resorbable polymer matrix, the method comprising the steps of: a) providing a plurality of said glass fibers that are compatible with said matrix polymer; b) providing a mixture comprising the matrix polymer in a solvent; c) applying the mixture onto the plurality of glass fibers; and d) removing the solvent from the mixture applied onto the plurality of glass fibers using an antisolvent to obtain the solid polymer composite material. The present invention relates to the above method, which comprises the steps of:
[0013] It has been found that the method of the present invention has many advantages compared to the use of conventional methods in which the polymer is used in the melt. The first advantage is that the matrix polymer does not need to be processed at melt temperature. This is attractive as it reduces the possibility of thermal degradation of the polymer. A further advantage is that by using the matrix polymer in a solvent, a low viscosity solution can be obtained with improved fiber spreading and fiber wetting. A further advantage of using a solvent-antisolvent combination is that the matrix polymer present in the final product may have a lower content of monomers and low molecular weight oligomers than the starting matrix polymer. Since it is the high molecular weight polymer that is responsible for the properties of the composite, it is believed that a low amount of low molecular weight components is advantageous.
[0014] Biocompatible and resorbable glass fibers are known in the art. In this context, the term "resorbable" means that the material does not significantly activate an inflammatory response during its degradation process, but is eliminated from the body through mineralization (i.e., breakdown and ionic release) and dissolution of the ionic products.
[0015] In the context of this specification, the term "composite" (sometimes also called polymer composite) refers to a composite material that includes glass fibers embedded in a polymer matrix.
[0016] Terms used in this application, unless otherwise defined, are those agreed upon at the consensus conference on biomaterials in 1987 and 1992: Williams, DF (ed.): Definitions in biomaterials Proceedings of a consensus conference of the European Society for Biomaterials, Chester, England. March 3-5, 1986. Elsevier, Amsterdam 1987, and Williams DF, Black J, Doherty PJ. Second consensus conference on definitions in biomaterials. In: Doherty PJ, Williams RL, Williams DF, Lee AJ (eds). Biomaterial-Tissue Interfaces. Amsterdam: Elsevier, 1992.
[0017] In the context of the present invention, the compatibility of the glass fiber with the matrix polymer refers to the interface between the glass fiber and the surrounding matrix polymer. It is therefore understood that the glass fiber is preferably compatible with the matrix polymer. Therefore, it is preferred that the surface of the glass fiber, which is essentially hydrophilic, is compatible with the matrix polymer in contact with the essentially hydrophobic surface of the glass. Typically, the glass fiber is covered with a coating or sizing layer to lower the surface energy. In the case of the concept of compatibility, this coating or sizing layer is considered as an integral part of the glass fiber. As a result, coated or sized glass fibers that are compatible with the matrix polymer layer mean that the coating or sizing layer is compatible with the matrix polymer, and therefore provides good interfacial adhesion for load-transfer. Thus, in a preferred embodiment, the resorbable glass fibers compatible with the matrix polymer are resorbable glass fibers having a coating or sizing layer on their surface that is compatible with the matrix polymer.
[0018] In the method of the present invention, a mixture is provided that contains the matrix polymer in a solvent. In the present invention, a solution is generally used, i.e., the polymer is completely dissolved in the solvent. The solvent is a fluid in which the matrix polymer dissolves at a concentration that results in a pourable solution with a dynamic viscosity that allows easy processing. By using a solution, a processable liquid can be obtained without resorting to high temperatures required for melting the polymer. The solution can be produced using any known method and equipment, such as, for example, providing a vessel containing the matrix polymer and the solvent, and mixing the matrix polymer and the solvent using a suitable polymer mixer. It is noted that the mixture may also contain solid components, such as hydroxyapatite or calcium phosphate.
[0019] The dynamic viscosity of the mixture when applied onto the glass fibers is preferably 10000 or less, more preferably 5000 or less, and most preferably 500 or less, pascal-seconds (Pa.s), where 1 Pa.s is equal to 1000 centipoise (cP), when measured at 18° C. The dynamic viscosity of the solution is preferably in the range of 1-1000 Pa.s., preferably 5-500 Pa.s., more preferably 20-200 Pa.s., when measured at 18° C. It is understood herein that the viscosity is measured according to ASTM D2196-20, for example using an Anton-Paar ViscoQC Rotational Viscometer.
[0020] The required viscosity of the mixture at the time of contacting with the glass fibers can be ensured through controlling various parameters, among them the nature of the solvent, the concentration of the polymer, and the aging of the solution. It is well known that polymer solutions, especially concentrated polymer solutions, can age over time, resulting in orientation of the polymer and thus an increase in viscosity. In such cases, agitating the mixture, for example through stirring, shaking or vibration, and optionally slightly increasing the temperature, can reduce the aggregation of the polymer and thus the viscosity.
[0021] The concentration of the matrix polymer in the mixture is typically at least 1 wt%, preferably at least 5 wt%, more preferably at least 10 wt%, even more preferably at least 20 wt%. The concentration of the matrix polymer in the mixture is typically no more than 70 wt%, preferably no more than 50 wt%, more preferably no more than 35 wt%, even more preferably no more than 25 wt%.
[0022] In the context of the present invention, the term "anti-solvent" is used to denote a fluid or liquid that is miscible with the solvent, but in which the matrix polymer does not dissolve under the conditions prevailing during the presence of the anti-solvent. In other words, the anti-solvent used for solidification of the matrix polymer is miscible with the solvent, but the matrix polymer does not dissolve in the anti-solvent. Since the solvent and the anti-solvent are miscible, the addition of the anti-solvent can be used to reduce the solubility of the matrix polymer in the liquid.
[0023] In the method of the present invention, the addition of the antisolvent ensures that the matrix polymer solidifies. This solidification process of the present invention can also be described in terms of solvent quality, where the term "solvent quality" is used in its conventional sense to indicate how well a compound dissolves in a solvent. The solvent quality of the solvent for the matrix polymer is good, meaning that the matrix polymer can be dissolved in a large amount in the solvent. On the other hand, the solvent quality of the antisolvent for the matrix polymer is poor, meaning that the amount of polymer that will dissolve in the antisolvent is small. When an antisolvent is added to the mixture of matrix polymer and solvent on glass fibers, the solvent quality of the solvent on the glass fibers is reduced. As a result, the solvent quality of the solvent mixture for the matrix polymer is deteriorated by adding the antisolvent, and the polymer gels and solidifies by phase separation from the mixed solvent. As a result, the matrix polymer precipitates on the glass fibers, resulting in a solid polymer composite.
[0024] It is understood that the preferred choice of solvent depends on the matrix polymer used and the preferred anti-solvent (mixture) depends on the choice of solvent and matrix polymer. Matrix polymers are known in the art and any known matrix polymer can be used for the method according to the invention, so long as it is suitable for the present invention, i.e., at least biocompatible and resorbable, and compatible with glass fibers.
[0025] Preferably, the matrix polymer is a polyester, more preferably, the matrix polymer is a thermoplastic polyester, and most preferably, the matrix polymer is a lactide-based polyester. Additionally or alternatively, the matrix polymer may be selected from the group consisting of polylactide (PLA), poly-L-lactide (PLLA), poly-DL-lactide (PDLLA), polyglycolide (PGA), poly(ε-caprolactone) (PCL), copolymers of glycolide, glycolide / trimethylene carbonate copolymer (PGA / TMC), lactide / tetramethylglycolide copolymer, lactide / trimethylene carbonate copolymer, lactide / d-valerolactone copolymer, lactide / ε-caprolactone copolymer, L-lactide / DL-lactide copolymer (PLDLA), glycolide / L-lactide copolymer (PLGA), polylactide-co-glycolide, lactide / glycolide / trimethylene carbonate terpolymer, lactide / glycolide / ε-caprolactone terpolymer, PLA / polyethylene oxide copolymer. poly(β-hydroxypropyl)-1,4-dioxane-2,5-diones, polyhydroxybutyrates (PHB), PHB / β-hydroxyvalerate copolymers (PHB / PHV), poly-β-hydroxypropionates (PHPA), poly-p-dioxanones (PDO), poly-d-valerolactone-poly-ε-caprolactone, poly(ε-caprolactone-DL-lactide) copolymers, methyl methacrylate-N-vinylpyrrolidone copolymers, polyesteramides, oxalic acid polyesters, polydihydropyrans, polyalkyl-2-cyanoacrylates, polyurethanes (PU), polyvinyl alcohols (PVA), polypeptides, poly-β-malic acid (PMLA), poly-β-alkanoic acids, polycarbonates, polyorthoesters, polyphosphates, poly(ester anhydrides), and mixtures thereof.
[0026] Polylactide (PLA), poly-L-lactide (PLLA), poly-DL-lactide (PDLLA), polyglycolide (PGA), poly(ε-caprolactone) (PCL), copolymer of glycolide, glycolide / trimethylene carbonate copolymer (PGA / TMC), lactide / tetramethylglycolide copolymer, lactide / trimethylene carbonate copolymer, lactide / d-valerolactone copolymer, lactide / ε-caprolactone copolymer, L-La It may be preferable to use a matrix polymer selected from the group including lactide / DL-lactide copolymer (PLDLA), glycolide / L-lactide copolymer (PLGA), polylactide-co-glycolide, lactide / glycolide / trimethylene carbonate terpolymer, lactide / glycolide / ε-caprolactone terpolymer, PLA / polyethylene oxide copolymer, poly(ε-caprolactone-DL-lactide) copolymer, and combinations thereof. It may be particularly preferable to use a matrix polymer selected from the group including polylactide, poly(lactide-co-glycolide), poly(lactide-co-ε-caprolactone), polyglycolide (PGA), and poly(ε-caprolactone) (PCL), and combinations thereof.
[0027] In a preferred embodiment of the method, the ratio between the intrinsic viscosity of the matrix polymer in the solid polymer composite material and the intrinsic viscosity of the (virgin) matrix polymer provided in b) is between 0.5 and 1.5, preferably between 0.8 and 1.2, most preferably between 0.9 and 1.1. The intrinsic viscosity (IV) property is known in the art and can be determined by dilute solution viscosity measurements, for example according to the ASTM 2857 method using a glass capillary viscometer.
[0028] Generally, the intrinsic viscosity of the matrix polymer in the solid polymer composite material does not deviate significantly from the viscosity of the matrix polymer before it is combined with the solvent.
[0029] The solvent preferably comprises or consists of acetone, chloroform, dichloromethane, tetrahydrofuran and / or ethyl acetate. In all cases, a relatively pure solvent is preferred. It is therefore considered preferred that the solvent consists of at least 80% by weight, in particular at least 90% by weight, more in particular at least 95% by weight, even more in particular at least 98% by weight, or at least 99% by weight, of acetone, chloroform, dichloromethane, tetrahydrofuran or ethyl acetate. When the solvent comprises or consists of acetone, the anti-solvent is preferably selected from water, C1-C6 alcohols, water-acetone mixtures, water-C1-C6 alcohol mixtures and water-acetone-C1-C6 alcohol mixtures. When the solvent comprises or consists of chloroform or dichloromethane, the anti-solvent is preferably selected from C1-C6 alcohol-chloroform mixtures, C1-C6 alcohol-dichloromethane mixtures, C1-C6 alcohols, or mixtures thereof. When the solvent comprises or consists of ethyl acetate, the anti-solvent is preferably selected from water, C1-C6 alcohols, water-acetone mixtures, water-C1-C6 alcohol mixtures, water-acetone-C1-C6 alcohol mixtures, and acetone.
[0030] Of course, there are many (further) useful combinations of polymers, solvents and antisolvents. Table 1 below shows a list of preferred matrix polymers for the process according to the invention, together with preferred choices of solvents and antisolvents corresponding to said preferred matrix polymers. It is considered that all combinations listed in Table 1 should be examples according to the invention, but it is emphasized here that this Table 1 is non-exhaustive, in the sense that further combinations are also possible and other polymers, solvents and / or antisolvents can be used for the process of the invention.
[0031] [Table 1]
[0032] The method of the invention can be extended with one or more additional steps after the solid polymer composite is obtained in step d). A preferred example of such a step may be represented as e) and comprises shaping the solid polymer composite obtained in step d) to form, for example, a medical device, for example an implantable device. Examples of suitable shapes are tapes, strands, (cannulated) rods, tubes, pellets, granules or filaments. Other examples of possible devices, for example orthopedic implants, are screws, nails, wires, pin wires, anchors, cable ties or wire ties, plates and screw systems, as well as external fixators or filaments. These are just a few examples of orthopedic implants based on polymer composites. The choice of material will depend on the specific requirements of each device, for example biocompatibility, mechanical strength and durability.
[0033] Here, "molding" is understood to mean manipulating the polymer composite in such a way that the final product of the composite has a certain desired shape. This can be achieved by any known method, for example pressing (e.g. forcing into a shape), thermoforming, cutting, slitting, calendaring and / or rolling. It is understood here that several operations can be combined, for example several rolling steps resulting in further thinning of the rolled tape, and optionally cutting the rolled tape to obtain strips. Other molding methods include, for example, injection molding, compression molding, stereolithography, extrusion, or thermoforming. In the case of injection molding, the polymer composite is melted and injected into a mold, which is then cooled and solidified to form the device. In compression molding, the polymer composite is placed into a mold and subjected to high pressure and heat, whereby stereolithography is a process in which a laser is used to selectively harden the polymer composite material layer by layer to create 3D shapes. Extrusion is a process in which the polymer composite is melted and forced through a die to create a long continuous shape that can then be cut to size. Thermoforming is a process in which the polymer composite is heated and formed into a mold using vacuum or pressure. The choice of molding method will depend on factors such as the desired shape, production volume, and material properties of the polymer composite being used.
[0034] In the method of the present invention, the solvent may preferably be partially evaporated before adding the antisolvent, which offers the advantage that less antisolvent may be required to remove the solvent from the composite. Therefore, the method of the present invention preferably includes a step c2) of evaporating at least a portion of the solvent from the mixture applied onto the glass fibers.
[0035] Step d) of removing the solvent from the mixture with an antisolvent to obtain the solid composite material can be carried out by contacting the glass fibres provided in the mixture with the antisolvent, for example by passing the glass fibres through a bath of antisolvent. Other methods will be apparent to those skilled in the art. The solid composite material is recovered from the bath and the remaining antisolvent can be removed, for example through evaporation.
[0036] The glass fibers may suitably have a diameter of from 5 to 30 μm, preferably from 6 to 20 μm, as measured using ASTM D1577-01, option C. In one embodiment, the glass fibers used in the present invention preferably have a diameter of less than 30 μm, particularly less than 25 μm, more particularly less than 20 μm, and in some embodiments less than 15 μm.
[0037] In one embodiment, the glass fibers are applied in the form of glass fiber bundles. In one embodiment, the glass fiber bundles have a linear density of 5 to 5000 tex, preferably 20 to 1300 tex, more preferably 25 to 750 tex, even more preferably 50 to 500 tex, and even more preferably 70 to 300 tex, throughout the bundle, as measured according to ASTM D1577-01 option Ai. The term "linear density" corresponds to the weight of a length of the glass fiber bundle, with the unit tex corresponding to the weight in grams per 1000 meters of fiber.
[0038] The glass fiber bundles that can be used in the present invention preferably have at least 50 fibers, preferably at least 100 fibers, more preferably at least 150 fibers, even more preferably at least 200 fibers. As a maximum value, 5000 fibers, more particularly 3000 fibers, can be mentioned.
[0039] In one embodiment, the glass fiber bundle used in the present invention has a coefficient of variation of the diameter of the glass fibers in the glass fiber bundle of 15% or less, particularly 10% or less. The coefficient of variation may be 8% or less, or 6% or less. In some embodiments, it has been found that the coefficient of variation may be 3% or less, which is a measure of the diameter being quite uniform. The coefficient of variation is determined as follows: the diameter of 30 glass fibers is determined from a glass fiber bundle. The average diameter and standard deviation are calculated. The coefficient of variation is the standard deviation divided by the average diameter, and is expressed as a percentage.
[0040] In a preferred embodiment, the glass fiber is a bioactive glass fiber. Bioactive glass fibers are known in the art and are designed to induce or modulate bioactivity. Bioactive materials are often surface-active materials that can interact with mammalian tissue. Bioactive glasses may further be designed to elute ions or other chemicals that result in osteoconductive, osteoinductive, anti-infective and / or angiogenic benefits.
[0041] The glass fibres can be silica-based, boron-based or phosphorus-based glass fibres. Preferably, the glass fibres are silica-based.
[0042] The glass fibers used in the present invention preferably have a composition comprising a network former and a network modifier, where the molar ratio of the network former to the network modifier is between 1 and 4, preferably between 1.5 and 3.5, more preferably between 2 and 3. It has been observed that a ratio according to such a range, in particular one of the preferred ranges, results in good glass quality, in particular suitable for fiber formation.
[0043] The glass fibers are preferably made of oxides of silicon, such as silica (SiO), oxides of boron, such as diboron trioxide (B2O3) and boron suboxide (BO), and oxides of phosphorus, such as phosphorus trioxide (PO3) and phosphorus pentoxide (PO5 or PO4). 10 The glass fibers preferably contain a network former selected from the group consisting of oxides of sodium, such as Na2O or Na2O 2、 and a network modifier selected from oxides of magnesium, e.g., MgO, and oxides of calcium, e.g., CaO. More preferably, the glass fibres comprise some network formers and some network modifiers.
[0044] The glass fibers are preferably 50 to 75% by weight of SiO2, in particular 55 to 75% by weight, more in particular 60 to 75% by weight, 0-15% by weight of B2O3, 0.5 to 5% by weight of P2O5, in particular 0.5 to 4% by weight, more in particular 0.5 to 3% by weight, 5 to 20% by weight of Na2O, 0 to 25% by weight of CaO, in particular 2 to 25% by weight, more in particular 5 to 25% by weight, 0-10% by weight of MgO, 0-1 wt.% LiO, 0 to 15% by weight of K2O, in particular 0 to 10% by weight, more in particular 0 to 4% by weight, 0-4% by weight of SrO, 0-5 wt.% Al2O3, and 0-5% by weight Fe2O3 (not counting the sizing agent, if present).
[0045] In one embodiment, the glass fiber has a composition including by weight 60-75% SiO2, 0-15% B2O3, 0.5-3% P2O5, 5-20% Na2O, 5-25% CaO, 0-10% MgO, 0-1% Li2O, 0-4% K2O, 0-4% SrO, 0-5% Al2O3, and 0-5% Fe2O3 (not counting sizing agents, if any).
[0046] In one embodiment, the glass composition comprises less than 10 wt.%, in particular less than 5 wt.% B2O3. In one embodiment, the glass composition comprises 7-20 wt.% Na2O. In one embodiment, the glass composition comprises 2-8 wt.% MgO. In one embodiment, the glass composition comprises 5-15 wt.% CaO.
[0047] The glass fibres preferably have a tensile strength, measured by a tensile test according to DIN EN ISO 5079, of 1000 to 3000 MPa, preferably 1200 to 2500 MPa, more preferably 1400 to 2200 MPa.
[0048] The glass fibres preferably have a modulus of elasticity of 20 to 100 GPa, preferably of 35 to 85 GPa, more preferably of 50 to 70 GPa, measured by a tensile test according to DIN EN ISO 5079 "Determination of breaking force and elongation at break of individual fibres" (ISO 5079:2020).
[0049] Attractive glass fibers and glass fiber bundles for use in the present invention are described in a patent application having the same filing and priority date as this application, entitled "Resorbable and biocompatible glass fiber bundle having a well-defined diameter and process for making such," the text of which is incorporated herein by reference in its entirety.
[0050] In a preferred method, multiple mixtures containing a matrix polymer and a solvent are applied onto the glass fiber. This is understood to include multiple applications of the same mixture, successive applications of multiple mixtures having the same matrix polymer at different concentrations, and / or successive applications of different mixtures having different matrix polymers and / or different solvents. Ideally, the multiple mixtures are applied by performing b) and c) multiple times (e.g., 2 times, 5 times, 10 times) in succession.
[0051] The present invention therefore relates to a method for obtaining a solid composite comprising a plurality of biocompatible and resorbable glass fibers embedded in a biocompatible and resorbable matrix polymer, the method comprising the steps of: a) providing a plurality of biocompatible and resorbable glass fibers; b) providing a first mixture comprising a first biocompatible and resorbable matrix polymer that is compatible with the glass fibers and a first solvent; c) applying the first mixture onto the plurality of glass fibers; d) optionally removing the first solvent from the first mixture using a first antisolvent; e) optionally at least partially drying the first matrix polymer coated glass fibers; f) providing a second mixture comprising a second biocompatible and resorbable matrix polymer that is compatible with the glass fibers and / or the first biocompatible and resorbable matrix polymer and a second solvent; g) applying the second mixture onto the plurality of glass fibers; h) removing the solvent from the mixture using an antisolvent to obtain the solid composite. It is understood that the present invention relates to the above method comprising the steps of:
[0052] It is understood that the antisolvent in step h) must be an antisolvent for at least the second mixture, and is preferably an antisolvent for the first mixture and the second mixture. If step d) is omitted, the antisolvent in step h) is preferably an antisolvent for the first mixture and the second mixture. It is further understood that the first matrix polymer and the second matrix polymer may be the same polymer or different polymers. Also, the first solvent and the second solvent may be the same solvent or different solvents.
[0053] It should be noted that, if desired, between steps c) and d) and / or between steps g) and h), the solvent may be partially removed from the system by evaporation before applying the antisolvent.
[0054] In a preferred embodiment, the polymer concentration in the second mixture is higher than the polymer concentration in the first mixture. The polymer concentration in the second mixture is preferably at least 1.5 times that of the first mixture, preferably at least 2 times that of the first mixture, more preferably at least 2.5 times that of the first mixture.
[0055] A particular advantage of the method of the present invention is that it can produce a composite with a lower Yellowness Index (YI) compared to the method according to the current technology. Thus, preferred methods are those in which the difference in Yellowness Index between the matrix polymer provided in step b) and the obtained composite is less than 20, preferably less than 10, more preferably less than 5, even more preferably less than 2. The term "YI" is known in the art and is preferably determined according to ASTM E313. Yellowness is often caused by the use of heat, which is not necessary in the method according to the present invention.
[0056] Preferably, the composite material has a Yellowness Index (YI), measured according to ASTM E313, of less than 30, preferably less than 20, more preferably less than 15, even more preferably less than 10.
[0057] Another advantage of the present invention is that it is possible to produce composites with a very high glass fiber content. Thus, the method of the present invention is preferred for obtaining solid composites comprising at least 60% by weight of a plurality of biocompatible and resorbable glass fibers, preferably at least 70% by weight of a plurality of biocompatible and resorbable glass fibers, more preferably at least 80% by weight of a plurality of biocompatible and resorbable glass fibers, and even more preferably at least 90% by weight of a plurality of biocompatible and resorbable glass fibers.
[0058] A further advantage of the method according to the invention is that it produces a smaller number of voids and / or bubbles at the glass / matrix interface compared to conventional melting techniques. These voids and / or bubbles can scatter light and thus give the composite an off-white appearance and / or a whiteish color. Voids or bubbles often form along the glass fibers, resulting in a white streak appearance. It is presumed that in conventional melting techniques, the molten matrix polymer does not wet the glass fiber surface sufficiently, resulting in the formation of voids and bubbles. The solvent method of the invention does not suffer from this drawback and produces composites without voids or bubbles, or at least with a very small number of voids or bubbles, resulting in a composite with a more homogeneous appearance.
[0059] The method of the invention allows the incorporation of additives, such as bioactive additives, into the composite. Thus, in a preferred embodiment, the method according to the invention further comprises embedding an additive, such as an active pharmaceutical ingredient (API) or a mineral ingredient, into the composite.
[0060] The present invention further relates to a complex obtainable by the method of the invention.The present invention also relates to a complex obtained by the method of the invention.
[0061] The invention further relates to a composite comprising a plurality of glass fibers embedded in a polymer matrix compatible with the plurality of glass fibers, the glass fibers and the polymer matrix being biocompatible, resorbable and preferably bioactive, the composite having a monomer content of less than 1% by weight. Preferably, the monomer content is less than 0.5% by weight, more preferably less than 0.2% by weight, even more preferably less than 0.1% by weight. The monomer content is calculated on the amount of polymer matrix. These monomers can come from different sources, but an important source is degradation due to the high temperatures required to prepare the composite (i.e. the high temperatures required to obtain a polymer melt suitable for extrusion). It is beneficial to have a low monomer content, since high monomer levels show a loss of strength as well as other mechanical properties. This is particularly relevant in the case of implants that are to be placed in the body of a mammal, preferably a human, for long periods of time. An attractive feature of the method of the invention is that it is possible to produce composites with a low monomer content. On the one hand, this is caused by the fact that the polymer does not need to reach the melting temperature, thus avoiding thermal degradation. On the other hand, the use of a solvent-antisolvent combination itself reduces the presence of monomer in the polymer matrix, since the extraction of residual monomer from the complex into the solvent and / or antisolvent is an additional purification step of the matrix polymer.
[0062] Preferably, the glass fibers in the composite are at least partially coated with a sizing layer, in particular a sizing agent that includes a compatibilizer that is compatible with the matrix polymer. Thus, in a preferred embodiment, the matrix polymer compatible resorbable glass fibers are resorbable glass fibers having a sizing layer on their surface that is compatible with the matrix polymer. An attractive sizing and its application method are described in a patent application entitled "Resorbable glass fiber coated with a sizing and method for preparing such" having the same filing date and priority date as this application, the text of which is incorporated herein by reference in its entirety. Further sizing compositions are known in the art and need not be further described herein.
[0063] In one embodiment, at least 10% of the structural units of the compatibilizer are identical to the structural units of the matrix polymer. This is one way to ensure good compatibility between the glass fiber and the matrix material. In one embodiment, at least 20%, at least 40%, or at least 60% of the structural units of the compatibilizer are identical to the structural units of the matrix polymer. In one embodiment, both the compatibilizer and the matrix polymer contain at least 20% by weight, particularly at least 30% by weight, of lactide units. In one embodiment, both the compatibilizer and the matrix polymer contain at least 20% by weight, particularly at least 30% by weight, of caprolactone units. In another embodiment, the compatibilizer and the matrix polymer contain at least 20% by weight, particularly at least 30% by weight, of glycolide units.
[0064] Preferably, the complex includes an additive, such as an active pharmaceutical ingredient (API) or a mineral ingredient, embedded in the complex.
[0065] Preferably, the composite has a low number of bubbles and / or voids. It is understood that the bubbles and voids in the composite give the composite a milky and whiteish appearance. Thus, preferably, the composite according to the present invention is translucent, more preferably transparent. It is understood here that translucency and transparency are optical properties and relate to the passage of visible light, whereby visible light is light having a wavelength within the visible spectrum of about 380 to about 750 nanometers. In one embodiment, the composite has a visible light transmittance of at least 50%, in particular at least 70%, more particularly at least 80%. It is preferred that the composition is radiopaque, which means that it blocks X-rays. It is understood that X-rays refer to high energy radiation having a wavelength of about 10 pm to about 10 nm. The radiopaqueness of the composite can be achieved by suitable selection of the glass fibers. Radiopaque composites are an attractive option for implantable medical devices because their degradation can be monitored in vivo via X-rays.
[0066] In the composite, the glass fibers or glass fiber bundles may be present as continuous fibers and / or chopped fibers. When chopped fibers are used, they generally have a length in the range of 1 mm to 50 mm, in particular 1 mm to 25 mm, more in particular 1 mm to 20 mm, even more in particular 2 mm to 10 mm, and most in particular less than 4 mm and more than 1 mm.
[0067] In one embodiment, the medical device comprises a unidirectional composite tape. Glass fiber-based tapes are known in the art. They comprise a biodegradable polymer and a plurality of continuous glass fibers aligned in one direction, where the fibers are aligned along the length of the tape. The tape generally has a width of at least 2 times, particularly at least 5 times, more particularly at least 10 times, the thickness of the tape. The length of the tape generally is at least 10 times, particularly at least 100 times, the width of the tape. The thickness of the tape is preferably less than 0.3 mm, more preferably less than 0.2 mm, even more preferably less than 0.15 mm. The length of the tape is preferably at least 1 m, more preferably at least 5 m, even more preferably at least 10 m. The third dimension (i.e., width) is preferably 0.5 to 10 cm, more preferably 0.8 to 5 cm, even more preferably 1 to 2.5 cm. A composite tape can be obtained, for example, by spreading the fibers of a glass fiber bundle, contacting the glass fibers with a liquid polymer matrix and solidifying the matrix. Unidirectional composite tapes preferably have a matrix content of 2-40% by weight, in particular 5-30% by weight, more in particular 5-25% by weight, in a particular embodiment 10-20% by weight. As regards the nature of the matrix and the nature of the glass fibers, the preferred embodiments mentioned elsewhere also apply here.
[0068] In one embodiment, the medical device comprises multiple layers, one or more of the layers comprising one or more composite tapes.
[0069] Thus, in one embodiment, the composite is molded in the form of a unidirectional composite tape, as described above. In an alternative embodiment, the composite is molded as strands, rods, pellets or granules. Strands / rods are fiber-reinforced polymers, preferably in round shape with a diameter of 5-50 mm. Pellets are small sections of the length of the rods with a diameter of about 5-50 mm, and granules are small particles with a diameter of about 1-10 mm. The dimensions of the pellets or granules may be adapted to match the dimensions of the feed screw used in polymer processing techniques, such as injection molding.
[0070] Preferably, the intrinsic viscosity of the matrix polymer in the composite material is 1.5 to 4.0 dL / g, preferably 1.8 to 3.0 dL / g, more preferably 2.0 to 3.0 dL / g.
[0071] Generally, the polymer composite material has a Young's modulus (as tested by ASTM D7264 / D7264M) higher than that of the matrix polymer, preferably between 110% and 1000%, more preferably between 200% and 600%, and most preferably between 300% and 500% compared to the matrix polymer.
[0072] Preferably, the glass reinforced polymer composite material has a mechanical strength according to a three-point bend test (tested according to ASTM D7264 / D7264M) that is higher than the strength of the matrix polymer, preferably at least 110% compared to the matrix polymer, preferably at least 200% compared to the matrix polymer, and most preferably at least 400% compared to the matrix polymer when the applied force is perpendicular to the reinforcing fibers.
[0073] Preferably, the polymer composite has a glass fiber content, calculated on glass and polymer combined, of 5-95%, preferably 10-90%, more preferably 15-80%, even more preferably 20-70%, and most preferably 30-60% by weight. Alternatively, the composite preferably has a glass fiber content of at least 60%, more preferably at least 70%, even more preferably at least 80%, and even more preferably at least 90% by weight.
[0074] The composite according to the invention may contain, in addition to the glass fibres and the polymer, for example up to 30%, up to 20% or up to 10% by weight of further components. Examples of further components can be hydroxyapatite and calcium phosphates, such as tricalcium phosphates (TCP), e.g. β-TCP.
[0075] The glass-reinforced polymer composites according to the invention are particularly suitable for use in medical devices, such as medical implants. The invention therefore also relates to a medical device comprising a composite material according to the invention. Preferably, the medical device is an implant or scaffold comprising a composite material according to the invention.
[0076] As will be clear to one skilled in the art, different embodiments of the invention can be combined as long as they are not mutually exclusive.
[0077] All percentages used herein are by weight unless otherwise specified.
[0078] When amounts, concentrations, dimensions, and other parameters are expressed in the form of ranges, preferred ranges, upper values, lower values, or preferred upper and lower values, it is to be understood that any range that can be obtained by combining any upper value or preferred value with any lower value or preferred value is also specifically disclosed, regardless of whether the resulting range is expressly stated in the context.
[0079] The present invention will now be illustrated with reference to the following examples, without being limited thereto or by them.
[0080] Working Example
[0081] Measurement techniques
[0082] intrinsic viscosity Inherent viscosity (IV) is a measure for the average molecular weight of a polymer obtained from its dilute solution viscosity. It is based on comparing the time it takes for a sample solution to flow through a narrow tube (i.e. Ubbelohde) with the time it takes for a known pure solvent to flow through a tube of the same size. This is according to ASTM 2857.
[0083] To determine the IV, three solutions of matrix polymer at 2, 1 and 0.5 g / dL are prepared from the composite sample. These solutions are prepared by dissolving the composite sample in chloroform and subsequently filtering through a 0.2 μm filter to remove the glass fibers. The polymer concentration is corrected for the glass content determined using TGA. A blank solution containing only solvent is also prepared. The measuring tube is rinsed with the sample solution filtered using a 0.2 μm filter. The filtered sample solution is then filled between the two lines and placed in a water bath set at 25° C. The flow time t0 of the sample is then measured and the Hagenbach correction corrected t h Correct it with t g The sample t g and a blank t g Based on η rel =t g,サンプル / t g,ブランク The relative viscosity was calculated using the intrinsic viscosity η inh is η inh = ln(η rel) / C, where C is the concentration of the sample (g / dL). Thus, IV has the units dL / g.
[0084] The resulting intrinsic viscosity and sample weight are recorded appropriately in the batch record. The same process is repeated for the other solutions.
[0085] yellowness index Yellowness index (YI) was measured using a Konica Minolta Chromometer CR-410 according to ASTM D1925. The measurements were performed in triplicate. The instrument was calibrated with a standard calibration plate (No. 12133209) with Y=85.6, X=0.3150, y=0.3212.
[0086] Tape Dimensions The width was measured using a digital microscope. An image of the tape was taken and then the width was measured using Zen core version 2.5 software or Keyence microscope software. The thickness was measured using a wide-faced screw gauge (or caliper).
[0087] Three-point bending test Thin layers of prefabricated composite tape were packed and stacked in a uniform direction to create samples for testing. The number of tape layers depended on the required thickness of the composite. These composite layers were then heated above the melting point of the polymer (190-200°C) in a rectangular (100mm x 100mm) compression mold, pressed with a load of 12kN for 5 minutes, and then quenched to obtain composite plaques.
[0088] The composite plaques were then cut into rectangular coupons and tested according to ASTM D7264 / D7264M-15. A span to thickness ratio of 16:1 was used. Standard width: 13 mm, where the length of the sample piece was approximately 20% longer than the support span (10% on each side).
[0089] Loss on ignition by thermogravimetric analysis (TGA) The loss on ignition (LOI) technique is a suitable technique for determining the matrix content of glass fiber samples. A LECO 701 macro thermogravimetric analyzer (TGA) was used to determine the matrix content of 1±0.2 g samples. The test began by recording the sample in the software, followed by determining the initial (empty) crucible weight (with lid). Once the initial weight was measured, the samples were added to the crucibles in their respective positions, and the equipment determined the weight of the sample. The instrument was subsequently heated to 110° C. and maintained for 30 minutes. After 30 minutes, the equipment was heated to 565° C. at a rate of 25° C. / min and held at that temperature for 2 hours. Weights were determined at regular intervals while the instrument was running, and the % mass loss for each step was calculated and reported. In the first step (110°C), the moisture in the sample was measured without burning off any sizing from the fiber. At a higher temperature (565°C), the matrix content was obtained by burning off the sizing on the glass fiber.
[0090] Gas Chromatography (GC) Polymer from the composite sample (corresponding to 300 mg of polymer based on TGA data) was dissolved in 25 mL of chloroform and then filtered through a 0.2 μm filter. An Agilent 7820A GC system equipped with an autosampler (7650A) with an FID detector equipped with an Agilent DB-225 capillary column was used. The injector, detector, and column oven temperatures were set at 200° C. High purity nitrogen (99.999% purity) was used as the carrier gas. The injection volume was 1.0 μL with the autosampler. The injected sample solution was separated using the capillary column and detected using a flame ionization detector (FID). The peak area is a measure for the concentration.
[0091] Relative Gel Permeation Chromatography (GPC): A gel permeation chromatograph (Agilent 1200 series) was used to measure the relative number average and weight average molecular weights (M, respectively) of the compatibilizers against polystyrene standards. n and M w ) was used to measure the solubility of the amines. The GPC consisted of a guard column, two PL gel mixed D columns, and an evaporative light scattering detector (ELSD). Ethanol-stabilized HPLC grade chloroform (Biosolve) was used as the mobile phase at a flow rate of 1 mL / min, and the measurements were performed at 35°C. 15 mg of the compatibilizer sample was dissolved in 15 mL of chloroform and then filtered through a 0.45 μm filter before GPC analysis. The GPC system was calibrated using narrow polystyrene standards.
[0092] Comparative Example A - Preparation of Composite Tape Using Polymer Melt Multifilament glass fiber bundles (type NX-8) with a composition including 67.8 wt% SiO2, 1.5 wt% P2O5, 2.3 wt% B2O3, 9 wt% CaO, 5.4 wt% MgO, and 14 wt% Na2O were prepared by melt spinning using a 204 tip platinum bushing set-up, followed by in-line dip-coating of a dispersion including epoxy silane and a degradable and acid functional thermoplastic resin based sizing agent, and drying and curing on the glass fibers at 35-140° C. There are 204 fibers (also called filaments) per fiber bundle, and the fibers have an average diameter of approximately 11 micrometers as confirmed by SEM.
[0093] A polymer melt was prepared from Purasorb PLDL 7028 polylactide (from Purac America Inc., Lenexa, Kans.) and dried under vacuum at room temperature before use. The intrinsic viscosity of the polylactide copolymer chips was measured to be 2.8 dL / g.
[0094] Several of these multifilament, bioresorbable NX-8 glass fiber spools were aligned and individually wound in a creel via pultrusion from a horizontal axis at a speed of 1-3 m / min towards a twin belt puller (with PUR belts) which pulled the fiber through the polymer melt and provided the necessary force to unwind the spool in the creel.
[0095] The polymer melt was fed at a feed rate of 500-2000 g / hr by a twin-screw extruder delivering the PLDL 7028 melt to an electrically heated cross-head die at a maximum temperature of 235°C.
[0096] After the creel and before the crosshead die, the glass fiber bundle is passed under gentle tension over horizontal pins (set temperature 275° C.) to equalize tension and spread the warp, and then enter the feed side of the crosshead die.
[0097] In the crosshead die, the hot polymer melt comes into contact with the glass fiber warp while passing over and under stationary horizontal pins to further spread and wet. The prepreg is then passed through a slit die of the desired shape (circular for strands / pellets and rectangular for tapes) and geometry. In the case of tapes as the final product, the impregnated tape from the forming die was calendered under gentle pressure. The composite tape or strand was then air cooled before being taken up by a puller. After the puller, the consolidated tape or strand was collected on a spool. The round strand passed through the forming die and was pelletized using a strand pelletizer after passing through the puller. Various experiments were carried out using this method to investigate its feasibility. The results obtained are shown in Table 2 below.
[0098] Example 1 - Preparation of a composite tape with a poly(L-lactide) matrix
[0099] Purasorb PLDL 7020 (a polylactide copolymer having 70 mol % L-lactide and 30 mol % D-lactide, the polylactide copolymer having an intrinsic viscosity of 2.0 dL / g, from Purac America Inc., Lenexa, Kans.) was dissolved in three mixing vessels at three different concentrations (7, 12, and 20% w / w, respectively). The resorbable glass fibers were coated with a covalently bonded sizing agent comprising an epoxysilane reacted with an acid functional lactide-eps.-caprolactone copolymer (Mn 5.6, Mw 8 kg / mol as measured by relative GPC measurement), the resorbable glass fibers had a target composition of 67.8 wt% SiO2, 51.5 wt% P2O, 2.3 wt% B2O3, 9 wt% CaO, 5.4 wt% MgO and 14 wt% Na2O, and the resorbable glass fibers were pulled from a creel. The target total linear density of the combined fiber bundle was 2500 tex according to ASTM D1577-01 A, and the average fiber diameter was 14.7 μm.
[0100] The glass fibers were led from the creel through horizontal reeds and passed through various sections of a composite line with a chain of aligned modules. The line consisted of baths fed with either acetone or a polymer solution in acetone. In the first bath, excess and unreacted sizing agents were washed off and the sized glass fibers were spread with the help of uneven pins. A nicely spread wide fiber warp was produced. This warp of fibers was then introduced into a low-concentration (7% by weight) polymer solution bath, where all the fibers were coated with a thin layer of polymer solution. This coated warp was then air-dried and then introduced into a second medium-concentration (12%) polymer solution. The warp absorbed more polymer from the second bath and was subsequently air-dried. At this point, the so-called prepreg was collected on a spool and vacuum-dried overnight. The next day, the prepreg was placed on a creel and passed through a high concentration (20%) polymer solution bath. The exit of this bath was equipped with a rectangular die that helped to form the prepreg into the desired flat shape. The desired shaped product with the desired polymer / glass fiber ratio was then passed through a finishing section equipped with three solvent exchange baths. The first antisolvent bath contained a mixture of 70% acetone and 30% water at -10°C, the second antisolvent bath was 50% acetone / 50% water at -10°C, and the third antisolvent bath was 100% water at a temperature of 50°C. The product spent at least 90 seconds in each bath. After the third bath, the wet product was collected on a spool backed with polypropylene mesh. The spool was then vacuum dried for three days to remove residual acetone and water. After drying for three days, the product was hot-calendared and slit into tapes of the desired specifications (width and thickness). A radiopaque and transparent composite was obtained. Various experiments were carried out using this method to investigate its feasibility. The results obtained are shown in Table 2 below.
[0101] As can be seen from Table 2 below, the method of the present invention allows for a much higher fiber content compared to the prior art method. Moreover, it is shown that the drop in IV during manufacture is much lower for the composite of Example 1 than for the comparative example. Also, there is less monomer generation in the case of the composite of Example 1. Therefore, it is concluded that there is less degradation of the matrix polymer during the manufacturing process of the composite when the method of the present invention is used compared to the known method. In addition, it was found that the spreading of the matrix polymer around the glass fiber is improved, which increases the contact area between the glass fiber and the matrix, resulting in fewer voids, bubbles, and white streaks. A larger contact area means improved load transfer in the composite produced, which is useful for making stronger composites. Fewer bubbles, voids, and white streaks enhance the transparency of the composite, since bubbles scatter light and cause a milky appearance.
[0102] Example 2 - Preparation of composite tape with poly(L-lactide) matrix Purasorb PL 24 (poly(L-lactide) homopolymer with an intrinsic viscosity of 2.4 dL / g) was dissolved in chloroform at 10% (w / w) in a mixing vessel until completely dissolved. One single bundle of resorbable sized glass fibers with a target composition of 67.8% by weight SiO2, 51.5% by weight PO2, 2.3% by weight β2O3, 9% by weight CaO, 5.4% by weight MgO, and 14% by weight Na2O was pulled from a supply creel. The fibers were coated with a sizing agent based on epoxy silane and acid functional lactide ε-caprolactone copolymer (Mn 5.6, Mw 8 kg / mol as measured by relative GPC) covalently bonded onto the glass fiber surface. The linear density of the glass fiber bundle was 140 tex (or g / km), which corresponds to an average fiber diameter of 11 micrometers. The fibers were passed through different sections of a custom-made reel-to-reel applicator consisting of different modules containing the polymer and antisolvent (ethanol) baths. The polymer bath was filled with a (10 wt%) polymer solution in chloroform. In the polymer bath, the glass fibers were spread with the help of static pins and impregnated with the matrix polymer with the help of submerged rollers. Then, a narrow and flat prepreg strand was sent back into the antisolvent bath through guide rollers, which were also submerged in the antisolvent (ethanol). The line speed was kept constant at 1 m / min throughout the experiment. After the antisolvent (ethanol) bath, the prepreg was tack-free and almost dry before reaching the winder. Then, the prepreg was collected on a spool. The collected spools were loaded onto a let-off creel and the prepreg was passed through the line for a second pass. The prepreg was coated with more polymer via rollers and sent back into the anti-solvent (ethanol) bath as in the first pass. The flat strands were then collected on a spool. The spool was finally dried in a vacuum oven to remove residual solvent (CHCl3) and ethanol.
[0103] The obtained tapes were subsequently analyzed and their properties are shown in Table 3 below. From the comparison of the monomer content and Mn before and after tape preparation, it can be concluded that there is very little degradation of the matrix polymer during preparation. Also, the obtained tapes were very white, indicating low YI.
[0104] Example 3 - Preparation of composite tape with poly((LD)-lactide) matrix
[0105] Purasorb PLDL 7020 (a polylactide copolymer with 70 mol% L-lactide and 30 mol% D-lactide, the polylactide copolymer having an intrinsic viscosity of 2.0 dL / g) was dissolved in acetone in a mixing vessel at 10 wt%. Powdered tricalcium phosphate (ground α-TCP from Cam Bioceramics (lot# 13CAM02.97)) was slowly added to the polymer solution at 10 wt%. A bundle of sized resorbable glass fibers with a target composition of 67.8 wt% SiO2, 1.5 wt% P2O5, 2.3 wt% B2O3, 9 wt% CaO, 5.4 wt% MgO, and 14 wt% Na2O was pulled from a creel. The fibers were coated with a sizing agent based on epoxy silane and acid functional lactide-eps.-caprolactone copolymer (Mn 5.6, Mw 8 kg / mol as measured by relative GPC) covalently bonded onto the glass fiber surface. The average linear density of the glass fiber bundle was 140 tex (or g / km) and the corresponding average fiber diameter was 11 micrometers. The fibers were passed through different sections of a custom-made reel-to-reel applicator consisting of different modules containing polymer and antisolvent baths. The polymer bath was filled with a polymer solution formulated with TCP in acetone. In the polymer bath, the individual glass fibers were spread with the help of static pins and impregnated with the matrix polymer / TCP with the help of submerged rollers. The narrow and flat prepreg strand was then sent back into the antisolvent bath via guide rollers that were also immersed in ethanol. For proof of concept, the antisolvent bath consisted of 100% ethanol at room temperature. After the antisolvent bath, the prepreg was tack-free and nearly dry before reaching the winder. The prepreg was then collected on a spool. The collected spool was loaded onto a let-off creel, and the prepreg was threaded through the line for a second pass.The prepreg was further coated with polymer / TCP via rollers and sent back into the anti-solvent (alcohol) bath as in the first pass. The flat strand was then collected again on a spool. The spool was finally dried in a vacuum oven to remove residual dichloromethane and ethanol. The line speed was kept constant at 1 m / min throughout the experiment.
[0106] The obtained tapes were subsequently analyzed and their properties are shown in Table 3 below. From the comparison of the monomer content and Mn before and after tape preparation, it can be concluded that there is very little degradation of the matrix polymer during preparation. Also, the obtained tapes were very white, indicating low YI.
[0107] [Table 2]
[0108] [Table 3]
[0109] Example 4 - Providing a sizing having polycaprolactone as a compatibilizer on glass fibers and incorporating the coated fibers into a polycaprolactone matrix to form a polycaprolactone glass fiber reinforced composite which is further processed to form a composite plaque.
[0110] 1. Preparation of Silane-treated Glass Fibers The hydrolyzed silane solution was prepared by dissolving 117 g of 3-glycidyloxy-propyltriethoxysilane in 10 kg of ASTM Type II purified water at 50° C. for 90 minutes. The hydrolyzed silane solution was then applied in-line via a kiss roller onto freshly drawn glass fibers as they were formed in the melt spinning process. The glass composition was the same as that applied in Example 5. The resulting fiber bundle was wound onto a core for further processing. The wet glass fibers were air-dried and then vacuum-dried at room temperature to bring the moisture level to less than 1000 ppm. The dried glass fibers were heat-treated at 90° C. for 4 hours to covalently bond the silane to the hydroxyl groups on the glass fiber surface.
[0111] 2. Preparation of aqueous PC(IV 0.15) nanodispersion 40 g of acid functionalized polycaprolactone with IV of 0.15 dL / g (measured according to ASTM 2857) and acid value of 39.4 mg KOH / g was dissolved in 1600 g of acetone for 1 hour. After complete dissolution, triethylamine (TEA, from Sigma Aldrich) was added in a 1:1 molar ratio to the acid to neutralize the acid end groups. After stirring for 15 minutes, the polymer solution was gradually added to ASTM Type II purified water. After 24 hours of evaporation to remove the acetone, an aqueous nanodispersion with a solid content of about 3 wt% was obtained. The average particle size (z-average) measured by DLS (Malvern ZetaSizer-nano) was found to be 37 nanometers, with a D90 of 39 nm.
[0112] 3. Preparation of sized glass fibers of PC(IV 0.15) The silane-treated glass fibers (having an average diameter of 16 microns) obtained in step 1 above were further treated with the compatibilizing polymer (PC, IV 0.15 dL / g) prepared in step 2 above by passing them in a continuous manner through a polymer nanodispersion bath in an off-line reel-to-reel sizing applicator system. The line speed was 5 m / min. The sized fibers were collected on another perforated stainless steel (SS) core. Subsequently, the fibers were vacuum dried at room temperature and then cured at 90° C. for 16 hours to promote the reaction between the acid end groups of the compatibilizer and the epoxy groups of the silane already covalently bonded to the glass surface. The TEA present at the reaction sites acted as a catalyst and was finally removed by applying a vacuum.
[0113] Once cured, the PC-sized glass fiber samples were tested for the presence of a sizing layer, which is a PC (IV 0.15) compatibilizer, via the TGA loss-on-ignition method. The results confirmed the presence of 1±0.5 wt.% sizing on the glass fibers.
[0114] 4. Preparation of Composite Tapes Comprising Polycaprolactone Polymer and Fibers Sized with Polycaprolactone Compatibilizer A 10 wt% solution of high molecular weight polycaprolactone (Purasorb PC17, IV 1.7 dL / g, commercially available from Corbion Purac) was prepared in acetone at 50°C. A bundle of sized PC fibers (576 filaments) obtained in step 3 was coated with polymer by passing it through a polymer solution bath with a continuous reel-to-reel applicator system. The polymer solution bath was equipped with rollers and pins to spread the fibers for better wetting. The solvent was removed by passing the coated fibers through an antisolvent (ethyl alcohol) bath at room temperature with a line speed of 2 m / min, followed by air drying for 24 hours. After drying, the polymer-coated fibers appeared as a thin and narrow tape. The coated and dried fibers were analyzed for fiber / polymer content via a LECO, TGA701 heat loss method. The polymer content was 14.2% by weight.
[0115] 5. Composite plaques obtained by compression molding a composite containing polycaprolactone and coated glass fibers The composite tapes obtained in step 4 above were cut into long strips of 100 mm length, and a certain amount was stacked in a uniform direction and spread into the cavity of a preheated mold to prepare samples for mechanical testing. On the coated fiber stack, an additional polymer (Purasorb PC17, Tm 60°C) film was added as a top layer to make 50 wt% of the fiber in the final molded part. The mold cavity was 100 mm x 100 mm x 1 mm. These coated fiber bundles and polymer film layers were then heated above the softening temperature of the polymer, pressed, and subsequently cooled and removed from the mold. Composite plaques were obtained and used for analytical purposes.
[0116] 6. Mechanical Testing of the Composite The composite plaques from step 5 above were cut into rectangular coupons (50x13x1mm; LxWxT) and subjected to flexural property testing (3-point-bending test) according to ASTM D7264 / D7264M-15 using a Lloyd universal mechanical tester equipped with a 3 point bend fixture and a 2.5 kN load cell. A span to thickness ratio of 16:1 was used. With a standard width of 13 mm, the length of the specimen was approximately 20% longer than the support span (10% on each side). The average strength for the six samples tested was 147±7.6 MPa (a 600% improvement over the base polymer strength of 23 MPa) and elastic modulus was 6.46±0.68 GPa (a 58-fold improvement over the base polymer strength of 110 MPa). The samples tested were analyzed for fiber content via TGA heat loss method and the average fiber content of the composite was found to be 50.4 wt%.
[0117] Example 5 - Providing glass fibers with poly(DL-lactide) (PDL) as a compatibilizer and incorporating the coated fibers into a poly(DL-lactide) matrix to form a poly(DL-lactide) glass fiber reinforced composite material which is further processed to form a composite plaque.
[0118] Epoxy-functional, silane-treated glass fibers were prepared as described in Example 4 above.
[0119] 30 g of acid functionalized poly(DL lactide) (50 / 50) polymer with IV of 0.4 dL / g and acid value of 4.1 mg KOH / g was dissolved in 1500 g of acetone for 1 hour. After complete dissolution, TEA was added at a molar ratio of 1:1.3 to the acid to neutralize the acid end groups. After stirring the solution for 15 minutes, the polymer solution was slowly added to ASTM Type II purified water. After 24 hours of evaporation to remove the acetone, an aqueous dispersion of about 3 wt% was obtained. The average particle size (z-average) measured by DLS (Malvern ZetaSizer-nano) was found to be 30 nanometers, with a D90 of 24 nm.
[0120] The silane-treated glass fibers were further treated with compatibilizing polymer in an off-line reel-to-reel sizing applicator system by passing the glass fiber bundle through a bath of the above-mentioned polymer nano-dispersion in a continuous manner. The line speed was 5 m / min. The sized fibers were collected on another perforated SS core. The fibers were vacuum dried at room temperature and then cured at 90°C for 16 hours to promote the reaction of the -COOH end groups of the compatibilizer polymer with the epoxy ends of the silanes already covalently bonded to the glass surface. The TEA present at the reaction sites acted as a catalyst and was finally removed by applying a vacuum.
[0121] Once cured, the glass samples were tested for the presence of a sizing layer via the TGA loss on ignition method, and the results confirmed the presence of 1±0.5% sizing by weight on the glass fibers.
[0122] A 10 wt% solution (IV 2.0 dL / g) of high molecular weight poly(DL lactide) was prepared in acetone. A bundle (576 filaments) of the above sized fibers (having an average diameter of 16 microns) was coated with high molecular weight poly(DL lactide) by passing it through a polymer solution bath with a continuous reel-to-reel applicator system. The polymer solution bath was equipped with rollers and pins to spread the fibers for better wetting. The solvent was removed by passing the coated fibers through an antisolvent (ethyl alcohol) bath at room temperature. The line speed was 1 m / min. The coated fibers were air-dried for 24 hours. After drying, the coated fibers appeared as a thin and narrow tape. The coated and dried fibers were analyzed for fiber / polymer content via a LECO TGA701 heat loss method. The polymer content was 15.4 wt%.
[0123] The resulting composite tapes were cut into long strips of 100 mm length, and a certain amount was stacked in a uniform direction and spread into the cavity of a preheated mold to prepare samples for mechanical testing. On the coated fiber stack, an additional polymer (Purasorb PLDL7020) film was added as a top layer to make 50 wt% fiber in the final molded part. The mold cavity was 100 mm x 100 mm x 1 mm. These coated fiber bundles and polymer film layers were then heated above the softening temperature of the polymer, pressed, and subsequently cooled and removed from the mold. Composite plaques were obtained and used for analytical purposes.
[0124] The composite plaques were then cut into rectangular coupons (50x13x1 mm; LxWxT) and subjected to bending property testing (3-point-bending test) according to ASTM D7264 / D7264M-15 using a Lloyd universal mechanical tester equipped with a 3 point bend fixture and a 2.5 kN load cell. A span to thickness ratio of 16:1 was used. With a standard width of 13 mm, the length of the specimen was approximately 20% longer than the support span (10% on each side). The average strength for the six samples tested was 491.3±38.6 MPa (446% improvement from the base polymer's strength of 110 MPa) and elastic modulus was 12.72±1.5 GPa (374% improvement from the base polymer's strength of 3.4 GPa). The samples tested were analyzed for fiber content via TGA heat loss method and the average fiber content of the composite was found to be 52% by weight.
[0125] Example 6 - Providing glass fibers with a sizing agent having poly(DL-lactide / glycolide) (PDLG) as a compatibilizer and incorporating the sized fibers within a poly(DL-lactide / glycolide) matrix to form a poly(DL-lactide / glycolide) glass fiber reinforced composite material, which is further processed to form a composite plaque.
[0126] Epoxy-functional, silane-treated glass fibers were prepared as described in Example 4 above.
[0127] 30 g of acid functionalized poly(DL lactide / glycolide) 50 / 50 from Corbion with IV of 0.4 and acid value of 4.1 mg KOH / g was dissolved in 1500 g of acetone for 1 hour. After complete dissolution, triethylamine was added in a 1:1.3 molar ratio to the acid to neutralize the acid end groups. After stirring the solution for 15 minutes, the polymer solution was slowly added to ASTM Type II purified water. After 24 hours of evaporation to remove the acetone, an aqueous dispersion of about 3 wt% was obtained. The average particle size (z-average) measured by DLS (Malvern ZetaSizer-nano) was found to be 46 nanometers, with a D90 of 46 nm.
[0128] The silane-treated glass fiber was further treated with the above-mentioned polymer nano-dispersion in an off-line reel-to-reel sizing applicator system by passing the glass fiber through a bath of the above-mentioned polymer nano-dispersion in a continuous manner. The line speed was 5 m / min. The sized fibers were collected on another perforated SS core. The fibers were vacuum dried at room temperature and then cured at 90°C for 16 hours to promote the reaction of the -COOH end groups of the compatibilizer polymer with the epoxy ends of the silane already covalently bonded to the glass surface. The TEA present at the reaction sites acted as a catalyst and was finally removed by applying a vacuum.
[0129] Once cured, the glass samples were tested for the presence of a sizing layer via the TGA loss on ignition method, and the results confirmed the presence of a 1±0.5 wt. % coating on the glass fibers.
[0130] A 10 wt% solution of high molecular weight poly(DL lactide / glycolide) 85 / 15 with an IV of 2.3 dL / g was prepared in acetone at 50°C. A bundle (576 filaments) of sized fibers (having an average diameter of 16 microns) of the above PDLG was coated with PDLG 85 / 15 by passing it through a polymer solution bath with a continuous reel-to-reel applicator system. The polymer solution bath was equipped with rollers and pins to spread the fibers for better wetting. The solvent was removed by passing the coated fibers through an anti-solvent (alcohol) bath at room temperature. The line speed was 2 m / min. The coated fibers were air-dried for 24 hours. After drying, the coated fibers appeared as a thin and narrow tape. The coated and dried fibers were analyzed for fiber / polymer content via a LECO TGA701 heat loss method. The polymer content was 32.6 wt%.
[0131] The resulting composite tapes were cut into long strips of 100 mm length, and a certain amount was stacked in a uniform direction and spread into the cavity of a preheated mold to prepare samples for mechanical testing. On the coated fiber stack, an additional polymer (Purasorb PLDG85 / 15) film was added as a top layer to make 50 wt% fiber in the final molded part. The mold cavity was 100 mm x 100 mm x 1 mm. These coated fiber bundles and polymer film layers were then heated above the softening temperature of the polymer, pressed, and subsequently cooled and removed from the mold. Composite plaques were obtained and used for analytical purposes.
[0132] The composite plaques were cut into rectangular coupons (target 50x13x1 mm; LxWxT) and subjected to flexural property testing (3-point-bending test) according to ASTM D7264 / D7264M-15 using a Lloyd universal mechanical tester equipped with a 3 point bend fixture and a 2.5 kN load cell. A span to thickness ratio of 16:1 was used. With a standard width of 13 mm, the length of the specimen was approximately 20% longer than the support span (10% on each side). The average strength of the six samples tested was measured to be 770.7±131 MPa (770% improvement from the base polymer's strength of 100 MPa) and the modulus of elasticity was measured to be 23.9±5.4 GPa (570% improvement from the base polymer's strength of 4.2 GPa). The samples tested were analyzed for fiber content via TGA heat loss method and the average fiber content of the composite was found to be 55.7 wt%.
Claims
1. 1. A composite comprising a plurality of glass fibers in a compatible polymer matrix, wherein the glass fibers and the polymer matrix are biocompatible, resorbable and preferably bioactive, and the composite has a monomer content, calculated on the polymer matrix, of less than 1% by weight, preferably less than 0.5% by weight, more preferably less than 0.2% by weight, and even more preferably less than 0.1% by weight.
2. 2. The composite according to claim 1, wherein the composite has a Yellowness Index (YI), measured according to ASTM E313, of less than 30, preferably less than 20, more preferably less than 15, most preferably less than 10, and / or the composite is translucent, preferably transparent, preferably radiopaque.
3. 3. A composite according to claim 1 or 2, wherein the composite is in the form of a unidirectional composite tape or in the form of strands, rods, pellets or granules, in particular in the form of a unidirectional tape.
4. 4. The composite according to claim 1, wherein the intrinsic viscosity of the matrix polymer in the composite is from 1.5 to 4.0 dL / g, preferably from 1.8 to 3.0 dL / g, more preferably from 2.0 to 3.0 dL / g.
5. A medical device, such as an implant or scaffold, comprising the composite of any one of claims 1 to 4.
6. A method for producing a solid polymer composite comprising a plurality of biocompatible and resorbable glass fibres embedded in a biocompatible and resorbable matrix polymer, in particular a composite according to any one of claims 1 to 5, comprising the steps of: a) providing a plurality of biocompatible and resorbable glass fibers that are compatible with said matrix polymer; b) providing a mixture comprising the matrix polymer in a solvent; c) applying the mixture onto the plurality of glass fibers; and d) removing the solvent from the mixture applied onto the plurality of glass fibers using an antisolvent to obtain the solid polymer composite material. The method comprising the steps of:
7. 7. The method according to claim 6, wherein the solid polymer composite is shaped, preferably into a tape, strand, (cannulated) rod, tube, pellet, granule or filament.
8. 8. The method according to claim 6 or 7, wherein the solvent is partially evaporated after being applied onto the glass fibres.
9. The matrix polymer is a thermoplastic polyester, in particular polylactide (PLA), poly-L-lactide (PLLA), poly-DL-lactide (PDLLA), polyglycolide (PGA), poly(ε-caprolactone) (PCL), copolymers of glycolide, glycolide / trimethylene carbonate copolymer (PGA / TMC), lactide / tetramethylglycolide copolymer, lactide / trimethylene carbonate copolymer, lactide / d-valerolactone copolymer, lactide / ε-caprolactone copolymer, L-lactide / DL-lactide copolymer (PLDLA), glycolide / L-lactide copolymer (PDLA), 9. The method according to claim 6, wherein the polymer is selected from polylactide, poly(lactide-co-glycolide), poly(lactide-co-ε-caprolactone), polyglycolide (PGA) and poly(ε-caprolactone) (PCL) and combinations thereof.
10. providing a second mixture comprising a second matrix polymer and a second solvent; applying the second mixture onto the plurality of glass fibers having the matrix polymer applied thereto; and Optionally partially removing the second solvent from the second mixture applied onto the plurality of glass fibers having the matrix polymer applied thereto using a second antisolvent to obtain the solid polymer composite material; The method according to any one of claims 6 to 9, comprising:
11. The method according to any one of claims 6 to 10, wherein the polymer concentration in the second mixture is higher than in the previously applied mixture.
12. A method according to any one of claims 6 to 11, wherein the method comprises removing residual solvent and / or anti-solvent by evaporation.
13. 13. The method according to any one of claims 6 to 12, wherein the ratio of the intrinsic viscosity of the matrix polymer in the solid composite to the intrinsic viscosity of virgin matrix polymer is from 0.70 to 1.30, preferably from 0.90 to 1.10, more preferably from 0.95 to 1.
05.
14. 14. The method of any one of claims 6 to 13, wherein the difference in Yellowness Index between the virgin matrix polymer and the resulting composite is less than 20, more preferably less than 10, as measured according to ASTM E313.
15. The method according to any one of claims 6 to 14, further comprising the step of embedding an additive, preferably an active pharmaceutical ingredient (API) or a mineral phase, into the complex.
Citation Information
Patent Citations
Bioactive glass composition
JP2008074698A
Biocompatible composite materials and their use
JP2012524569A
Fiber-reinforced biocomposite medical implants with high mineral content
JP2019518568A